Strongly absorbing molecules make tissue transparent: a new insight for understanding tissue optical clearing - Tingting Yu; Dan Zhu (Light: Science & Applications)
Abstract Optical imaging plays a central role in the field of biomedicine, but it suffers from the light scattering of tissues. The research group from Stanford University has reported a counterintuitive observation that strongly absorbing molecules could achieve optical transparency in live animals, providing a new insight for understanding tissue optical clearing. It empowers scientists to leverage optical imaging techniques for in vivo observation of a wide range of deep-seated structures and activities.